(untitled) (Plant Tissue Culture and Biotechnology, 2022)
An in vitro mass propagation protocol was developed for Gerbera (Gerbera jamesonii Bolus) var. orange using flower bud explants. The young (7 days) explants were found to be suitable for culture and highest (100%) callus induction was obtained in MS medium supplemented with 5.0 mg/l BAP with 1.0 mg/l NAA. The maximum shoot regeneration (95%) and the number of shoots (10) were observed in MS medium supplemented with 6.0 mg/l BAP with 0.3 mg/l NAA. The highest shoot multiplication frequency (95%) and the number of shoots (60) were obtained in MS medium supplemented with only 2.0 mg/l BAP. The well-developed highest number of roots (5.0) per plant and average root length (5.0 cm) with 100% root induction efficiency without callusing was recorded in the half strength of MS medium devoid of any hormonal supplement. Acclimatized in vitro grown plantlets were successfully transferred into the field condition. Plant Tissue Cult. & Biotech. 32(2): 217-226, 2022 (December)